(untitled) (Salduie, 2024)
Use-wear, traceological or functional analysis are part of a methodology applied to archaeological materials that allows, through the microscopic analysis of their surface, to determine the activities in which they have participated. In this paper, a historiographical approach to the discipline from its origins to the present day is carried out, focusing on the use-wear studies applied to prehistoric lithic industry.